2007
DOI: 10.1590/s1807-59322007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delirium on Mortality and Cognitive and Functional Performance Among Elderly People With Femoral Fractures

Abstract: Furlaneto ME, Garcez-Leme LE. Impact of delirium on mortality and cognitive and functional performance among elderly people with femoral fractures. Clinics. 2007;62(5):545-52. OBJECTIVE:To evaluate the evolution of cognitive and functional performance and mortality among elderly patients who were delirious during hospitalization due to femoral fracture. who did not present with delirium. There were six deaths, and 97 patients were discharged from the hospital. We obtained information on 85 of these patients fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
3
32
1
Order By: Relevance
“…Functional status before fracture, older age, male gender, and higher surgical risk increased the risk of mortality, whereas the use of antibiotics and physical therapy after surgery decreased the risk. Previous studies showed functional status before fracture [14,42,45,52], male gender [12,15,28,33,36,42,47], older age [10,15,28,36,43,47,50,52,55], and higher ASA scores predicted mortality in older patients [24,26,33,44,49] (Table 3), which is in agreement with our findings. In our study, we did not see a difference in mortality between patients undergoing arthroplasty versus patients undergoing osteosynthesis, which is in agreement with mortality reported by Garcia et al [15] and others [18,33,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Functional status before fracture, older age, male gender, and higher surgical risk increased the risk of mortality, whereas the use of antibiotics and physical therapy after surgery decreased the risk. Previous studies showed functional status before fracture [14,42,45,52], male gender [12,15,28,33,36,42,47], older age [10,15,28,36,43,47,50,52,55], and higher ASA scores predicted mortality in older patients [24,26,33,44,49] (Table 3), which is in agreement with our findings. In our study, we did not see a difference in mortality between patients undergoing arthroplasty versus patients undergoing osteosynthesis, which is in agreement with mortality reported by Garcia et al [15] and others [18,33,37].…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested the reason for this increased mortality after arthroplasty could be higher use of arthroplasty with older age, but so far the evidence is inconclusive [18,54]. Finally, many authors have reported the impact of comorbid conditions on mortality [10,12,14,28,36,37,42,46,47,[50][51][52], whereas we did not observe this. This might be attributable to our measurement of comorbid conditions.…”
Section: Discussioncontrasting
confidence: 73%
“…This study establishes an association between delirium after cardiac surgery and cognitive dysfunction by means of preoperative and serial objective assessments of cognitive function and state-of-the-art assessments of delirium, both of which were not, to our knowledge, used in previous studies. [33][34][35][36][37][38] With the aging of the patient population undergoing cardiac surgery and increases in survival after surgery, clinicians and patients are increasingly concerned with factors associated with quality of life, including cognitive status, as major outcomes of surgery. 11,15 Although a high proportion of patients undergoing cardiac surgery have cognitive impairment immediately after the surgery, impairment diminishes in the weeks and months after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the red series is very important among elderly people (18) . Relatively small impro- non-coronary disease patients is recommended, but attentiveness must be maintained since elderly people may present silent ischemia.…”
Section: Blood Transfusionmentioning
confidence: 99%
“…Delirium is a frequent complication during the postoperative period (18,22) . Approximately 30% of According to the DSM-IV, delirium is characterized by altered consciousness, difficulty in focusing attention, cognitive impairment and disorganized thinking, and it may be associated with perception disorders.…”
Section: Delirium During the Perioperative Periodmentioning
confidence: 99%